The New Criminology Revisited
XI, 302 p.
Keywords: In 1973 The New Criminology was published and quickly established itself as a key textbook in criminology, casting a major influence over a generation of scholars. It has remained in print ever since. This volume, published twenty-five years later, traces the major developments in the field including feminism, postmodernism, critical criminology and realism. The articles are by leading authorities from Britain, the United States and Australia and include Stan Cohen, Elliott Currie, Pat Carlen and Kerry Carrington as well as separate commentaries by the three original authors themselves: Ian Taylor, Paul Walton and Jock Young.